Free neighborhood classes for adults Enroll now : Classes in reading - writing - arithmetic - also art - music - psychology - language - social studies. - unknown (Ill. : Federal Art Project, WPA, 1937)
Poster from the Adult Education Program of the Chicago Board of Education announcing free education classes for adults, showing a man, wearing a suit, reading.